Mulheres na política sul-americana: condicionantes institucionais e culturais - Dalcin, Cinthia Carvalho (2022)
In most of the world, women’s access to political power is still a challenge. If we look at the global percentage of women in national parliaments, specifically lower chambers and unicameral parliaments, women occupy on average 26,5% of the positions. In the 1990s, the global average was around 10%. To promote and improve women’s representation, several countries adopted gender quotas. Latin American countries were some of the first to do so, having Argentina as pioneer in adopting legislative quotas. Ever since Argentina adopted the quotas in 1991, over a hundred countries have adopted some type of quota. Some countries were more successful than others. This dissertation seeks to explore the importance of institutional factors such as the electoral system, party system and quota laws in place and cultural factors such as the women’s movement in acquiring political rights and emancipation in South American countries. More specifically, in Argentina, Brazil, Colombia, Peru and Uruguay. These countries were chosen due to their historical and cultural similarities and sociological timelines. Some questions motivate this study: 1) Under which conditions were quotas adopted? 2) Once quotas were adopted, can we perceive any cultural differences in countries where the quotas were successful? 3) What about in countries were the quotas were not successful? To answer these questions about cultural changes, we use data from the World Value Survey (WVS) regarding societies perception of women’s rights and female leadership. Institutionally, we look at the quota laws, electoral system and percentage of women elected.